Nivel de conocimiento y calidad de autocuidado del adulto mayor con hipertension. Florencia de Mora 2014 - Echeverria De La Cruz, Yuli (2014)
The present study of investigation of descriptive type correlacional, carried out, with the purpose of determining the relation between level of knowledge and quality of autocare of the major adult with Arterial Hypertension, which they come to the Center of health The Effort, Florence of Default 2014.The sample universe was constituted by 67 major adults of both sexes. For the compilation of information it was in use, the survey on level of knowledge and quality of autocare of the major adult with arterial hypertension, the results allow to come to the following conclusions: 42 % of the major adults presents a level of average knowledge and 36 %, a level of high knowledge. 51 % of major adults presents a quality of average autocare and 27 % of quality of high autocare. There exists statistical significant relation between the level of knowledge and quality of autocare of the major adults with hypertension